BISNIS KOMODITAS TERLARANG DALAM PERSPEKTIF ETIKA BISNIS HUKUM EKONOMI SYARIAH - Putri Tri Cahyani; Syahrul Anwar; Dede Kania (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2024)
The rapid growth of the business world brings significant challenges in terms of legality and morality, particularly regarding the trade of prohibited commodities. Although such businesses are considered illegal in many countries, their circulation continues to expand. The trade in prohibited commodities, such as drugs, alcoholic beverages, and other forbidden products, not only violates national laws but also contradicts the principles of Sharia economic law. This study aims to examine how Sharia economic law views the trade of prohibited commodities from an ethical perspective and how Islamic norms can uphold moral principles and justice in global trade. The research employs a qualitative method with an in-depth literature review approach, drawing on various references related to commodity trade and Sharia economic law. The findings indicate that Sharia economic law emphasizes the importance of justice, welfare, and the prohibition of harmful practices such as usury (riba), uncertainty (gharar), and gambling (maysir). Any form of trade containing elements of harm (mafsadat) to society is prohibited in Islam. In conclusion, the Sharia economic law approach offers a strong ethical foundation to prevent the circulation of prohibited commodities and encourages the establishment of a more just and moral economic system.